Viver o Envelhecimento: Como a dependência física e/ou cognitiva influencia os níveis de frustração emocional nos idosos em ERPI: https://doi.org/10.60543/ts_iss.vi10.11612 ("Temas Sociais" Journal, 2026)
This article examines the influence of physical and/or cognitive dependence on the emotional frustration levels of older adults living in the Alvalade Nursing Home (ERPI). Developed within the framework of Social Work Internship IV and the Monographic Report, the study adopted a qualitative approach, using a questionnaire administered to 10 residents, complemented by direct and participant observation. The study aimed to understand how the degree of dependence influences emotional frustration by analysing the relationship between loss of autonomy, adaptation to institutionalisation, and the role of the social worker in promoting well-being. The findings indicate that loss of autonomy is the main factor associated with emotional frustration and reveal discrepancies between residents' perceptions of their own abilities and the data obtained through observation. The study concludes that Social Work interventions focused on promoting autonomy, active participation, and person-centred, humanised care contribute to improving the emotional well-being of institutionalised older adults.
Keywords: Ageing; Dependency; Emotional Frustration; Institutionalisation; Social Work; Older Adults.